Management of obstructive sleep apnea in Europe-A 10-year follow-up - Fietze Ingo; Laharnar Naima; Bargiotas Panagiotis; Basoglu Ozen K; Dogas Zoran; Drummond Marta; Fanfulla Francesco; Gislason Thorarinn; Gouveris Haralampos; Grote Ludger; Hein Holger; Jennum Poul; et al. (Elsevier, 2022)
Objective: In 2010, a questionnaire-based study on obstructive sleep apnea (OSA) management in Europe identified differences regarding reimbursement, sleep specialist qualification, and titration procedures. Now, 10 years later, a follow-up study was conducted as part of the ESADA (European Sleep Apnea Database) network to explore the development of OSA management over time.Methods: The 2010 questionnaire including questions on sleep diagnostic, reimbursement, treatment, and certification was updated with questions on telemedicine and distributed to European Sleep Centers to reflect European OSA management practice.Results: 26 countries (36 sleep centers) participated, representing 20 ESADA and 6 non-ESADA countries. All 21 countries from the 2010 survey participated. In 2010, OSA diagnostic procedures were performed mainly by specialized physicians (86%), whereas now mainly by certified sleep specialists and specialized physicians (69%). Treatment and titration procedures are currently quite homogenous, with a strong trend towards more Autotitrating Positive Airway Pressure treatment (in hospital 73%, at home 62%). From 2010 to 2020, home sleep apnea testing use increased (76%-89%) and polysomnography as sole diagnostic procedure decreased (24%-12%). Availability of a sleep specialist qualification increased (52%-65%) as well as the number of certified polysomnography scorers (certified physicians: 36%-79%; certified technicians: 20%-62%). Telemedicine, not surveyed in 2010, is now in 2020 used in diagnostics (8%), treatment (50%), and follow-up (73%). Conclusion: In the past decade, formal qualification of sleep center personnel increased, OSA diagnostic and treatment procedures shifted towards a more automatic approach, and telemedicine became more prominent.(c) 2022 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).